Desolation mountain [large type] : a novel - Krueger, William Kent (Krueger, William Kent. Cork O'Connor mystery, 2018)
There are more things in heaven and earth, Horatio, than are dreamt of in your philosophy. To Stephen O'Connor, Hamlet's dour observation is more than just words. All his life, he has had visions of tragedies to come. When he experiences the vision of a great bird shot from the sky, he knows something terrible is about to happen. The crash of a private plane on Desolation Mountain in a remote part of the Iron Lake Reservation, which kills a United States senator and most of her family, confirms Stephen's worst fears. Stephen joins his father, Cork O'Connor and a few Ojibwe men from the nearby Iron Lake reservation to sift through the smoldering wreckage when the FBI arrives and quickly assumes control of the situation. What seems like the end of the O'Connors' involvement is, however, only the beginning of a harrowing journey to understand the truth behind the Senator's death. As he initiates his own probe, Cork O'Connor stumbles upon a familiar face in Bo Thorson, a private security consultant whose unnamed clients have hired him to look quietly into the cause of the crash. The men agree to join forces in their investigation, but soon Cork begins to wonder if Thorson's loyalties lie elsewhere. In that far north Minnesota County, which is overrun with agents of the FBI, NTSB, DoD, and even members of a rightwing militia, all of whom have their own agendas, Cork, Stephen, and Bo attempt to navigate a perilous course. Roadblocked by lies from the highest levels of government, uncertain who to trust, and facing growing threats the deeper they dig for answers, the three men finally understand that to get to the truth, they will have to face the great menace, a beast of true evil lurking in the woods--a beast with a murderous intent of unimaginable scale.